2019
DOI: 10.1364/ol.44.005104
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale piezoelectric surface modulation for adaptive extreme ultraviolet and soft x-ray optics

Abstract: Extreme ultraviolet and soft X-ray wavelengths have ever-increasing applications in photolithography, imaging, and spectroscopy. Adaptive schemes for wavefront correction at such a short wavelength range have recently gained much attention. In this letter, we report the first demonstration of a functional actuator based on piezoelectric thin films. We introduce a new approach that allows producing a gradually varying surface deformation. White light interferometery is used to show the level of control in gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The piezoelectric stress coefficient, e 31 , is more practical to characterize the performance of most actual devices, though some devices include adaptive extreme ultraviolet and soft Xray optics. 50 For instance, the figures of merit for sensors and energy harvesters are represented by e 31 and dielectric constant. The effective piezoelectric stress coefficient, e 31,eff , is widely utilized to characterize the thin film piezoelectric property, which is calculated from the curvature of a cantilever due to the actuation of the piezoelectric film on top of the cantilever beam.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The piezoelectric stress coefficient, e 31 , is more practical to characterize the performance of most actual devices, though some devices include adaptive extreme ultraviolet and soft Xray optics. 50 For instance, the figures of merit for sensors and energy harvesters are represented by e 31 and dielectric constant. The effective piezoelectric stress coefficient, e 31,eff , is widely utilized to characterize the thin film piezoelectric property, which is calculated from the curvature of a cantilever due to the actuation of the piezoelectric film on top of the cantilever beam.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The piezoelectric stress coefficient, e 31 , is more practical to characterize the performance of most actual devices, though some devices include adaptive extreme ultraviolet and soft X-ray optics . For instance, the figures of merit for sensors and energy harvesters are represented by e 31 and dielectric constant.…”
Section: Resultsmentioning
confidence: 99%
“…Ferroelectric thin films are of high interest for applications such as ferroelectric memories and in microelectro­mechanical systems as sensors and actuators. In particular, PbTi 1– x Zr x O 3 (PZT) is favored because of its outstanding ferroelectric and piezoelectric properties. These functional properties of PZT thin films are highly dependent on several material properties, such as the stoichiometry, crystal orientation, and microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Hysteresis is a common challenge in the use of piezoelectric ceramics and thin films in applications such as sensors, actuators, ferroelectric memories, and energy harvesters. [ 1–8 ] Hysteresis can cause energy loss in energy harvesting devices or positioning inaccuracy in actuators. [ 9 ] Several studies have identified the viscous interaction of ferroelectric domains as the source of hysteresis and the associated dielectric/ferroelectric loss for sub‐coercive field excitations.…”
Section: Introductionmentioning
confidence: 99%